SISTEM AKUNTANSI PENJUALAN DENGAN METODE CASH AND CARRY PADA PT PERHUTANI (PERSERO) - Feni Ocktafianti; Melinda Malau; Desideria Regina (Fakultas Ekonomi Universitas Kristen Indonesia, 2016)
Sales of a product produced by the company is a determinant in corporate activities. This condition is motivating companies in the implementation of the accounting system of cash sales were good in order to get a good income. PT Perhutani (Persero) KBM Agribusiness III Pusbahnas have policies and objectives are used as a guide at the time of delivery of goods to ensure that goods ordered at the outlet received properly by ensuring input data and the delivery of goods has been done correctly and accurately. Perhutani company KBM III Pusbahnas air Agribusiness in Parung Panjang, Bogor. Where in selling honey KBM Agribusiness III Pusbahnas implement systems sales accounting method Cash and Carry. Purpose Cash and Carry in forestry was like retailers / agents buy honey perhutani with basic selling price and resell at a price per outlet or it could be said with if the retail buy honey perhutani it must immediately pay the honey.Keywords : Sales, System, Inventory